Porous carbon and silicon carbon material, preparation method thereof and application of porous carbon and silicon carbon material in lithium ion battery
The use of phenol metal salts in an in-situ template process addresses the challenges of porous carbon preparation, resulting in a highly ordered structure that enhances silicon-carbon material performance in lithium-ion batteries by improving silicon dispersion and cycle stability.
Patent Information
- Application Number
- CN202411325769.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-23
AI Technical Summary
Existing methods for preparing porous carbon for lithium-ion batteries face challenges such as complex processes, high costs, and poor pore size uniformity, leading to issues like low specific capacity, poor cycle stability, and reduced battery performance due to silicon particle aggregation and volume expansion.
A method using phenol metal salts as a carbon source through an in-situ template process to create a highly ordered porous carbon structure, with controlled particle sizes and pore distribution, facilitating uniform silicon deposition and reducing volume expansion.
The method results in a porous carbon material with high compaction density, initial efficiency, and long cycle life, improving the electrochemical performance of silicon-carbon materials by enhancing silicon dispersion and buffering volume changes.
Smart Images

Figure CN119191264A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a porous carbon, silicon-carbon material, a preparation method thereof, and an application thereof in lithium ion batteries. Background Art
[0002] Lithium-ion batteries play an increasingly important role in modern human daily and industrial activities. The performance indicators of negative electrode materials, including lithium storage capacity, initial charge and discharge capacity, and cycle stability, have a significant impact on battery energy density, coulombic efficiency, energy efficiency, and service life.
[0003] Graphite has the advantages of low cost, good consistency, low lithium desorption voltage, small lithium desorption voltage hysteresis, and good conductivity. It is currently the mainstream negative electrode material for lithium-ion batteries. However, limited by the interlayer lithium storage mechanism, the theoretical specific capacity of graphite negative electrode is only 372mAh / g, and the actual specific capacity is very close to the theoretical specific capacity, which makes it difficult to significantly improve the overall energy density of the battery. Therefore, new high-specific-capacity negative electrode materials are in urgent need of development. The alloying reaction product of silicon-based negative electrode and lithium ions is Li 4.4 Si, this reaction can contribute a specific capacity of up to 4200mAh / g, and is a new type of negative electrode material with great potential for high energy density lithium-ion batteries. However, silicon negative electrodes still face severe technical challenges. For example, silicon will undergo a volume expansion of more than 300% during the lithium insertion process, which will lead to pulverization of active particles, destruction of electrode structure, and electrical inactivation, thereby causing rapid decay of battery capacity. Not only that, the side reactions between the silicon-based negative electrode and the electrolyte will lead to the continuous growth of the solid electrolyte interface (SEI), reducing the coulombic efficiency and further exacerbating the battery performance decay. In addition, the silicon material itself has poor conductivity, which will also affect the charge and discharge performance of the battery.
[0004] At present, researchers have developed strategies such as nano-sizing, carbon coating, silicon oxide, pre-lithiation, and amorphization to solve the above problems of silicon negative electrode. Sand-ground silicon-carbon materials (obtained by sand-grinding carbon materials and silicon materials and then sintering at high temperature) have low capacity and poor cycle stability; pre-magnesium and pre-lithium silicon oxide have low first efficiency, high price, and unsatisfactory cycle stability; and the new silicon-carbon technology based on the adsorption and pyrolysis of silane in the pores of porous carbon to generate amorphous nano-silicon has the advantages of high specific capacity, high first efficiency, and good cycle stability. However, the current preparation method of porous carbon mainly includes carbonization and activation steps, among which the activation method mainly includes physical activation method (such as water vapor, carbon dioxide as activator) and chemical activation method (such as alkali, acid as activator). The porous carbon prepared by carbonization + activation method has the disadvantages of complex process, high cost, low yield, and poor pore size uniformity. Therefore, it is urgent to develop a new method for preparing porous carbon to solve the above problems. Summary of the invention
[0005] In view of the problems of complicated process, high cost and poor pore size uniformity in the existing porous carbon preparation process, the present invention provides a porous carbon, silicon-carbon material and preparation method and application in lithium-ion batteries. The present invention uses phenol metal salt as a carbon source and prepares a porous carbon material with high pore size order by an in-situ template method. The novel silicon-carbon material prepared by vapor deposition using the porous carbon material as a substrate has the advantages of high compaction density, high initial efficiency, high rate and long cycle life, and has broad application prospects in the field of lithium-ion batteries.
[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing porous carbon, comprising the following steps:
[0008] S1, calcining the phenol metal salt at 600°C to 1100°C for 1h to 5h under a protective atmosphere to obtain a carbon-based material;
[0009] S2, crushing the carbon-based material to a D50 value of 3 μm to 15 μm;
[0010] S3, testing the ash content of the crushed carbon-based material. If the ash content is ≤0.2%, directly proceed to S4; if the ash content is >0.2%, acid washing and water washing are performed on the crushed carbon-based material for several times until the ash content of the carbon-based material is ≤0.2% or the pH of the water washing liquid is <7;
[0011] S4, testing the oxygen content of the crushed carbon material, if the oxygen content is ≤0.05mmol / g, directly proceed to S5; if the oxygen content is >0.05mmol / g, calcining the crushed carbon material at 700℃~1200℃ for 0.5h~3h under protective atmosphere and then proceed to S5;
[0012] S5, testing the particle size of the carbon material in S4, if it meets the requirements of D0 of 1μm to 5μm, D50 of 3μm to 15μm, and D100 of 10μm to 30μm, no further processing is required; if it does not meet the above particle size requirements, the carbon material is crushed and graded until the particle size meets the requirements to obtain porous carbon.
[0013] Compared with the prior art, the method for preparing porous carbon provided by the present invention has the following advantages:
[0014] (1) The present invention uses phenol metal salt as a carbon source. During the carbonization process, the phenol groups will gradually cross-link to form an aromatic network and then form an amorphous carbon material, and the metal ions will combine with the oxygen element in the phenolic hydroxyl group to form a metal oxide. The metal oxide can act as an in-situ embedded alkaline pore-forming agent, and during the carbonization process, the metal oxide is limited by the carbon material barrier and cannot continue to fuse and grow, thereby forming extremely small nanoparticles (particle size <5nm). At the same time, the in-situ formed metal oxide is evenly dispersed in the carbon material. Further, the metal oxide etches the surrounding carbon material to form pores, thereby forming a highly ordered pore structure in the carbon material, and the pore size is consistent. When preparing silicon-carbon material, silane gas is more likely to enter the pores of porous carbon, which is beneficial to reduce the mass transfer resistance of silane gas, thereby facilitating the uniform dispersion and fixation of silicon particles, avoiding the aggregation of silicon particles, and reducing the floating silicon phenomenon;
[0015] (2) Phenol metal salts as carbon sources have a higher carbon retention rate than other organic acid metal salts, which can improve the yield of porous carbon;
[0016] (3) By controlling the carbonization temperature and time of the phenol metal salt, it is beneficial to regulate the pore size and pore structure of the porous carbon material so that its specific surface area is 1000m 2 / g~3000m 2 / g, with a total pore volume of 0.6 cm 3 / g~2cm 3 / g, the proportion of micropore volume to total pore volume is more than 80%, and the average pore diameter is 1.5nm to 3nm. The high proportion of micropores is conducive to the formation of smaller confined nano-silicon particles after silane adsorption and cracking. Smaller silicon particles are conducive to alleviating the volume expansion during the lithiation process, thereby improving the electrochemical performance of silicon-carbon materials;
[0017] (4) The present invention performs graded control on the particle size of porous carbon, so that its D0 is 1μm to 5μm, D50 is 3μm to 15μm, and D100 is 10μm to 30μm. A D0 value that is too small will result in an excessively large specific surface area of the porous carbon material, which will in turn increase the specific surface area of the prepared vapor-deposited silicon-carbon material, which will increase the lithium ions consumed in forming SEI, thereby reducing the initial coulombic efficiency of the silicon-carbon negative electrode; a D100 value that is too large will result in the inability to effectively deposit silicon particles in the pores inside the porous carbon, thereby reducing the amount of silicon deposition, and thereby reducing the specific capacity of the silicon-carbon material. In addition, a D100 value that is too large will also increase the diffusion distance of lithium ions, reducing the rapid charge and discharge performance of the silicon-carbon material;
[0018] (5) The highly ordered pore structure of porous carbon can serve as a supporting skeleton, reducing the volume expansion and contraction of silicon during the charging and discharging process, thereby improving the structural stability and cycle life of the material; at the same time, the highly ordered pore structure is conducive to carrier transport, increasing the electrochemical reaction rate of the electrode material, thereby improving the overall performance of the battery.
[0019] Furthermore, S1, the gas of the protective atmosphere is one or more of nitrogen, argon, helium, carbon dioxide or water vapor.
[0020] Preferably, in S1, the gas of the protective atmosphere is carbon dioxide or water vapor.
[0021] Carbon dioxide or water vapor can not only serve as a protective gas, but also as an activator to participate in the pore-forming process, further increasing the porosity and specific surface area of the porous carbon.
[0022] Further, in S1, the temperature is increased to 600°C to 1100°C at a rate of 2°C / min to 25°C / min, and preferably, the temperature increase rate is 5°C / min to 10°C / min.
[0023] Preferably, in S1, the calcination temperature is 800°C to 1000°C, and the calcination time is 2h to 4h.
[0024] Furthermore, in S1, the metal phenolate is one or more of lithium phenolate, sodium phenolate, potassium phenolate, magnesium phenolate, calcium phenolate, zinc phenolate, manganese phenolate, aluminum phenolate or iron phenolate.
[0025] As a specific embodiment of the present invention, in S1, the preparation method of the phenol metal salt comprises the following steps: adding phenol and a metal source to a solvent, mixing them evenly, and removing the solvent to obtain the phenol metal salt; wherein the metal source comprises one or more of metal oxides or hydroxides corresponding to lithium, sodium, potassium, magnesium, calcium, zinc, manganese, aluminum, and iron.
[0026] Furthermore, the solvent is water or an alcohol.
[0027] Furthermore, the molar ratio of the phenol to the metal element in the metal source is 1:1 to 1:3, preferably 1:1 to 1:2.
[0028] Furthermore, the concentration of phenol after being dissolved in the solvent is 2 mol / L to 10 mol / L, preferably 3 mol / L to 5 mol / L.
[0029] It should be noted that, during the dissolution or dispersion process, phenol and the metal source are protected by air atmosphere or inert atmosphere.
[0030] As a specific embodiment of the present invention, the solvent can be removed by heating, spray drying, flash evaporation or freeze drying, and air atmosphere or inert atmosphere protection is used during the solvent removal process.
[0031] As another specific embodiment of the present invention, in S1, the preparation method of the phenol metal salt comprises the following steps: adding phenol and a metal source to a solvent, reacting, and removing the solvent to obtain the phenol metal salt; wherein the metal salt comprises one or more of the corresponding elements or metal hydrides of lithium, sodium, potassium, magnesium, calcium, zinc, manganese, aluminum, and iron.
[0032] Furthermore, the above-mentioned solvent is water or an alcohol substance, such as anhydrous ethanol, methanol, etc.
[0033] Furthermore, the molar ratio of the phenol to the metal element in the metal source is 1:1 to 1:3.
[0034] Furthermore, the above reaction is carried out at room temperature, and the reaction time is not less than 0.5h.
[0035] As a specific embodiment of the present invention, the solvent can be removed by heating, spray drying, flash evaporation or freeze drying, and air atmosphere or inert atmosphere protection is used during the solvent removal process.
[0036] As another specific embodiment of the present invention, in S1, the preparation method of the phenol metal salt comprises the following steps: reacting molten phenol with a solid metal source in an air atmosphere or an inert atmosphere to obtain a phenol metal salt; wherein the solid metal source comprises one or more of metal oxides or hydroxides corresponding to lithium, sodium, potassium, magnesium, calcium, zinc, manganese, aluminum, and iron.
[0037] Furthermore, the reaction temperature is 45°C to 150°C, and the reaction time is not less than 0.5h.
[0038] Furthermore, the molar ratio of the phenol to the metal element in the metal source is 1:1 to 1:3.
[0039] The above-listed preparation methods of phenol metal salts are only several specific practicable methods, and the present invention includes but is not limited to the above methods.
[0040] Furthermore, in S3, the pickling uses one or more of hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, hydrobromic acid, phosphoric acid, perchloric acid, formic acid or acetic acid.
[0041] Further, in S4, the temperature is increased to 700°C to 1200°C at a rate of 2°C / min to 25°C / min, and preferably, the temperature increase rate is 5°C / min to 10°C / min.
[0042] Furthermore, in S4, the calcination temperature is 800° C. to 1000° C., and the calcination time is 1 h to 2 h.
[0043] Furthermore, in S4, the gas of the protective atmosphere is one or more of nitrogen, argon, helium, carbon dioxide or water vapor.
[0044] It should be noted that, in S4, an organic element analyzer may be used to test the oxygen content in the porous carbon.
[0045] Furthermore, in S5, D0 of the porous carbon is 2 μm to 4 μm, D50 is 5 μm to 10 μm, and D100 is 10 μm to 20 μm.
[0046] Further, in S5, the specific surface area of the porous carbon is 1500m 2 / g~2000m 2 / g, with a total pore volume of 0.8 cm 3 / g~1.2cm 3 / g, the proportion of micropore volume to total pore volume is 85% to 95%, and the average pore diameter is 1.7nm to 2.5nm.
[0047] In a second aspect, the present invention further provides a porous carbon prepared by the above-mentioned method for preparing the porous carbon.
[0048] In a third aspect, the present invention further provides a silicon-carbon material, comprising the porous carbon mentioned above.
[0049] In a fourth aspect, the present invention further provides a method for preparing a silicon-carbon material, comprising the following steps:
[0050] Step a, depositing silicon particles onto the surface and / or pores of the porous carbon by chemical vapor deposition to obtain a silicon-carbon material precursor;
[0051] Step b, subjecting the silicon-carbon material precursor to one-step carbon coating or two-step carbon coating to obtain a carbon-silicon material.
[0052] The preparation method of porous carbon provided by the present invention uses phenol metal salt as a carbon source. Compared with metal salts of other organic acids (such as gluconic acid, citric acid or benzoic acid, etc.), phenol metal salt has a higher carbon retention rate, which can improve the yield of porous carbon; in addition, the metal oxide formed by the metal ion and the phenol hydroxyl group is equivalent to an in-situ embedded alkaline pore-forming agent, which can be evenly distributed during the carbonization process and play a role in activating pores. Moreover, due to the obstruction of the carbon material, the metal oxide cannot continue to grow during the carbonization process, so extremely small nanoparticles are formed. After the metal oxide is removed during the carbonization or pickling process, a highly ordered pore structure dominated by micropores is formed in the porous carbon. The highly ordered pore size distribution can avoid the adverse effects of ultra-micropores where silicon cannot be deposited and large mesopores where silicon is over-deposited on the electrochemical performance of the silicon-carbon negative electrode. The particle size distribution of the porous carbon after graded treatment is within an appropriate range, so that the silicon-carbon material prepared with it as the substrate has the advantages of high compaction, high initial efficiency, high rate and high cycle life, providing a negative electrode material with excellent comprehensive performance for lithium-ion batteries and has high practical value.
[0053] As a specific embodiment of the present invention, the method for preparing the silicon-carbon material specifically comprises the following steps:
[0054] Step a, placing the porous carbon in a vapor deposition silicon device, introducing an inert gas, exhausting the oxygen in the device, heating to 450°C to 700°C, introducing a silicon source gas, reacting for 2h to 6h, stopping the introduction of the silicon source gas, adjusting the temperature to 500°C to 750°C, introducing a carbon source gas, reacting for 1h to 5h, stopping the introduction of the carbon source gas, and then cooling in an inert atmosphere to obtain a primary carbon-coated silicon-carbon material;
[0055] Step b, placing the primary carbon-coated silicon-carbon material in a carbon coating device, introducing an inert gas to expel oxygen, heating to 500°C to 750°C, introducing a carbon source gas, reacting for 1h to 5h, stopping the introduction of the carbon source gas, and then cooling in an inert atmosphere to obtain a secondary carbon-coated silicon-carbon material.
[0056] Furthermore, in step a, the inert gas is one or more of nitrogen, argon, helium or carbon dioxide.
[0057] Furthermore, in step a, the silicon source gas is one or more of monosilane, disilane, dichlorosilane or trichlorosilane.
[0058] Preferably, in step a, the silicon source gas is monosilane or disilane.
[0059] Furthermore, in step a, the introduction temperature of the silicon source gas is 500° C. to 600° C., and the reaction time is 3 h to 5 h.
[0060] Furthermore, in step a, a programmed temperature increase method is adopted, and the heating rate is 2°C / min to 25°C / min, preferably 5°C / min to 10°C / min.
[0061] Furthermore, in step a, the silicon source gas is introduced at a flow rate of 1 L / min to 5 L / min.
[0062] Preferably, in step a, the inlet flow rate of the silicon source gas is 2 L / min to 4 L / min.
[0063] Furthermore, in step a, the carbon source gas is one or more of methane, ethane, propane, butane, ethylene, propylene, acetylene or propyne.
[0064] Preferably, in step a, the carbon source gas is ethylene or acetylene.
[0065] Furthermore, in step a, the flow rate of the carbon source gas is 1 L / min to 4 L / min.
[0066] Preferably, in step a, the flow rate of the carbon source gas is 2 L / min to 3 L / min.
[0067] Furthermore, the temperature of the carbon source gas is 600°C to 700°C, and the reaction time is 2h to 3h. Furthermore, in step a, the inert gas is introduced at a flow rate of 5L / min to 30L / min.
[0068] Preferably, in step a, the inert gas is introduced at a flow rate of 10 L / min to 20 L / min.
[0069] Furthermore, in step b, the carbon source gas is one or more of methane, ethane, propane, butane, ethylene, propylene, ethylene or propyne.
[0070] Preferably, in step b, the carbon source gas is ethylene or acetylene.
[0071] Furthermore, in step b, the flow rate of the carbon source gas is 1 L / min to 4 L / min.
[0072] Preferably, in step b, the flow rate of the carbon source gas is 2 L / min to 3 L / min.
[0073] Furthermore, in step b, the inert gas is introduced at a flow rate of 5 L / min to 30 L / min.
[0074] Preferably, in step b, the inert gas is introduced at a flow rate of 10 L / min to 20 L / min.
[0075] Furthermore, in step b, a programmed temperature increase method is adopted, and the heating rate is 2°C / min to 25°C / min, and preferably, the heating rate is 5°C / min to 10°C / min.
[0076] It should be noted that in step b, the secondary carbon coating is not limited to the use of gaseous carbon sources, and a solid carbon source (such as solid asphalt, glucose, sucrose, cyclodextrin, citric acid, carbon nanotubes, graphene, Ketjen black, acetylene black, etc.) or a liquid carbon source (such as liquid asphalt, methanol, ethanol, etc.) can also be mixed evenly with the silicon-carbon material coated once in step a and then heat-treated to obtain a secondary coated silicon-carbon material. Among them, the heating rate, insulation temperature, and flow rate of the inert atmosphere for the heat treatment using a solid carbon source or a liquid carbon source are the same as those in step b, and the amount of the solid carbon source or the liquid carbon source added is 1% to 10% of the mass of the silicon-carbon material coated once in step a.
[0077] In a fifth aspect, the present invention also provides a negative electrode, comprising the silicon-carbon material.
[0078] In a sixth aspect, the present invention further provides the use of the above silicon-carbon material or the above negative electrode in the preparation of a lithium-ion battery.
[0079] In a seventh aspect, the present invention further provides a lithium-ion battery, comprising the above-mentioned silicon-carbon material or the above-mentioned negative electrode.
[0080] In an eighth aspect, the present invention further provides a battery module, comprising the above-mentioned lithium-ion battery.
[0081] The porous carbon prepared by the present invention has the advantages of high microporosity, uniform pore size and high order. When it is used for chemical vapor deposition to further prepare silicon-carbon materials, the resistance to the diffusion of silane gas in the porous carbon material is smaller, which is beneficial to improving the silicon deposition efficiency. At the same time, it is also beneficial to the uniform dispersion and fixation of silicon particles in the porous carbon pore structure, avoiding the aggregation of silicon particles, and through the limiting effect of the micropore pore size, the nucleation and growth of silicon particles can be effectively controlled, thereby preparing silicon particles of uniform size. The uniformly distributed silicon particles and the ordered pore structure are beneficial to improving the electrical conductivity and ion diffusion rate of the silicon-carbon material; in addition, the ordered pore structure of the porous carbon can buffer the volume change of silicon during the charging and discharging process, and improve the cycle stability and service life of the silicon-carbon material; the application of the above-mentioned silicon-carbon material in lithium-ion batteries helps to improve the electrochemical performance of electrochemical devices containing the silicon-carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] Figure 1 This is a schematic diagram of the process of preparing porous carbon material in Example 1 of the present invention. DETAILED DESCRIPTION
[0083] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0084] In order to better illustrate the present invention, further examples are given below.
[0085] Example 1
[0086] This embodiment provides a method for preparing a porous carbon material, which specifically includes the following steps:
[0087] S1, under a nitrogen atmosphere, dissolving phenol and sodium hydroxide in water at a molar ratio of 1:1, wherein the concentration of phenol is 3 mol / L, and heating the solution under a nitrogen atmosphere to remove water to obtain sodium phenolate;
[0088] S2, under a nitrogen atmosphere, heating the sodium phenolate prepared above to 800° C. at a rate of 5° C. / min, keeping the temperature for 3 h, and cooling to room temperature to obtain a composite material of carbon material and metal derivative;
[0089] S3, crushing the composite material to a D50 of 7 μm, testing the ash content to be greater than 0.2%, washing the crushed composite material with hydrochloric acid and water until the pH of the water washing liquid is 6.1, collecting the porous carbon and drying it;
[0090] S4, testing the oxygen content of the dried porous carbon to be greater than 5 mmol / g, heating the dried porous carbon to 900° C. at a rate of 5° C. / min under a nitrogen atmosphere, and keeping the temperature for 1.5 h to obtain deoxidized porous carbon;
[0091] S5, crushing and classifying the above deoxidized porous carbon to obtain a finished porous carbon with D0 of 2 μm, D50 of 7 μm, and D100 of 18 μm, which has a moisture content of 2.5% after being placed in air with a humidity of 50% at normal temperature and pressure for 3 days.
[0092] Example 2
[0093] This embodiment provides a method for preparing a porous carbon material, which specifically includes the following steps:
[0094] S1, under a nitrogen atmosphere, dissolving phenol and zinc oxide in water at a molar ratio of 1:1.5, wherein the concentration of phenol is 4 mol / L, and heating the solution under a nitrogen atmosphere to remove water to obtain zinc phenolate;
[0095] S2, under a nitrogen atmosphere, heating the zinc phenolate prepared above to 900° C. at a rate of 7° C. / min, keeping the temperature for 4 h, and cooling to room temperature to obtain a composite material of carbon material and metal derivative;
[0096] S3, crushing the composite material to a D50 of 5 μm, testing the ash content to be greater than 0.2%, washing the crushed composite material with hydrochloric acid and water until the pH of the water washing liquid is 6.8, collecting the porous carbon and drying it;
[0097] S4, testing the oxygen content of the dried porous carbon to be greater than 5 mmol / g, heating the dried porous carbon to 1000° C. at a rate of 10° C. / min under a nitrogen atmosphere, and keeping the temperature for 1 hour to obtain a deoxidized porous carbon;
[0098] S5, crushing and classifying the above deoxidized porous carbon to obtain a finished porous carbon with D0 of 4 μm, D50 of 5 μm, and D100 of 10 μm, which has a moisture content of 2.1% after being placed in air at normal temperature, pressure, and humidity of 50% for 3 days.
[0099] Example 3
[0100] This embodiment provides a method for preparing a porous carbon material, which specifically includes the following steps:
[0101] S1, under a nitrogen atmosphere, dispersing phenol and manganese hydroxide in water at a molar ratio of 1:2.5, wherein the concentration of phenol is 5 mol / L, and spray drying the solution under a nitrogen atmosphere to obtain manganese phenolate;
[0102] S2, under a nitrogen atmosphere, heating the manganese phenolate prepared above to 1000° C. at a rate of 8° C. / min, keeping the temperature for 2 h, and cooling to room temperature to obtain a composite material of carbon material and metal derivative;
[0103] S3, crushing the composite material to a D50 of 10 μm, testing the ash content to be greater than 0.2%, washing the crushed composite material with hydrochloric acid and water until the pH of the water washing liquid is 6.6, collecting the porous carbon and drying it;
[0104] S4, testing the oxygen content of the dried porous carbon to be greater than 5 mmol / g, heating the dried porous carbon to 800° C. at a rate of 6° C. / min in a nitrogen atmosphere, and keeping the temperature for 2 h to obtain deoxidized porous carbon;
[0105] S5, crushing and classifying the above deoxidized porous carbon to obtain a finished porous carbon with D0 of 3 μm, D50 of 10 μm, and D100 of 20 μm, which has a moisture content of 2.0% after being placed in air with a humidity of 50% at normal temperature and pressure for 3 days.
[0106] Example 4
[0107] This embodiment provides a method for preparing a porous carbon material, which specifically includes the following steps:
[0108] S1, under a nitrogen atmosphere, dissolving phenol and calcium oxide in water at a molar ratio of 1:3, wherein the concentration of phenol is 2 mol / L, and flash distilling the solution under a nitrogen atmosphere to obtain calcium phenolate;
[0109] S2, under a nitrogen atmosphere, heating the calcium phenolate prepared above to 600° C. at a rate of 2° C. / min, keeping the temperature for 5 h, and cooling to room temperature to obtain a composite material of carbon material and metal derivative;
[0110] S3, crushing the composite material to a D50 of 3 μm, testing the ash content to be greater than 0.2%, washing the crushed composite material with hydrochloric acid and water until the pH of the water washing liquid is 6.1, collecting the porous carbon and drying it;
[0111] S4, testing the oxygen content of the dried porous carbon to be greater than 5 mmol / g, heating the dried porous carbon to 700° C. at a rate of 2° C. / min under a nitrogen atmosphere, and keeping the temperature for 3 h to obtain a deoxidized porous carbon;
[0112] S5, crushing and classifying the above deoxidized porous carbon to obtain a finished porous carbon with D0 of 1 μm, D50 of 3 μm, and D100 of 15 μm, and the water content of the finished porous carbon is 2.7% after being placed in air with a humidity of 50% at normal temperature and pressure for 3 days.
[0113] Example 5
[0114] This embodiment provides a method for preparing a porous carbon material, which specifically includes the following steps:
[0115] S1, under a nitrogen atmosphere, dissolving phenol and sodium oxide in water at a molar ratio of 1:1, wherein the concentration of phenol is 10 mol / L, and freeze-drying the solution under a nitrogen atmosphere to obtain sodium phenolate;
[0116] S2, under a nitrogen atmosphere, heating the sodium phenolate prepared above to 1100° C. at a rate of 25° C. / min, keeping the temperature for 1 hour, and cooling to room temperature to obtain a composite material of carbon material and metal derivative;
[0117] S3, crushing the composite material to a D50 of 15 μm, testing its ash content>0.2%, washing the crushed composite material with hydrochloric acid and water until the pH of the water washing liquid is 6.3, collecting the porous carbon and drying it;
[0118] S4, testing the oxygen content of the dried porous carbon to be greater than 5 mmol / g, heating the dried porous carbon to 1200° C. at a rate of 25° C. / min under a nitrogen atmosphere, and keeping the temperature for 0.5 h to obtain deoxidized porous carbon;
[0119] S5, crushing and classifying the above deoxidized porous carbon to obtain a finished porous carbon with D0 of 5 μm, D50 of 15 μm, and D100 of 30 μm, which has a moisture content of 1.8% after being placed in air at normal temperature, normal pressure, and 50% humidity for 3 days.
[0120] Example 6
[0121] This embodiment provides a method for preparing a porous carbon material, which specifically includes the following steps:
[0122] S1, under a nitrogen atmosphere, dissolving phenol and potassium hydroxide in water at a molar ratio of 1:2, wherein the concentration of phenol is 6 mol / L, and spray drying the solution under a nitrogen atmosphere to obtain potassium phenolate;
[0123] S2, under a nitrogen atmosphere, heating the potassium phenolate prepared above to 950° C. at a rate of 10° C. / min, keeping the temperature for 4 h, and cooling to room temperature to obtain a composite material of carbon material and metal derivative;
[0124] S3, crushing the composite material to a D50 of 7 μm, testing the ash content to be greater than 0.2%, washing the crushed composite material with hydrochloric acid and water until the pH of the water washing liquid is 6.5, collecting the porous carbon and drying it;
[0125] S4, testing the oxygen content of the dried porous carbon to be greater than 5 mmol / g, heating the dried porous carbon to 850°C at a rate of 7°C / min under a nitrogen atmosphere, and keeping the temperature for 2 hours to obtain deoxidized porous carbon;
[0126] S5, crushing and classifying the above deoxidized porous carbon to obtain a finished porous carbon with D0 of 3 μm, D50 of 7 μm, and D100 of 18 μm, which has a moisture content of 2.4% after being placed in air at normal temperature, pressure and humidity of 50% for 3 days.
[0127] Example 7
[0128] This embodiment provides a method for preparing a silicon-carbon material, comprising the following steps:
[0129] Step a, weighing 1.5385 kg of the porous carbon prepared in Example 1, that is, the mass of the dry porous carbon without water is 1.5 kg, transferring it to a vapor deposition silicon equipment, introducing nitrogen, the nitrogen flow rate is 30 L / min (the nitrogen flow rate is maintained until the temperature drops to room temperature), exhausting oxygen until the oxygen content is less than 0.5%, heating to 550° C. at a rate of 5° C. / min, introducing monosilane, the monosilane flow rate is 2 L / min, the introduction time is 5 h, stopping the introduction of monosilane, and heating to 600° C. at a rate of 5° C. / min, starting to introduce acetylene, the acetylene flow rate is 2 L / min, the introduction time is 3 h, stopping the introduction of acetylene, and naturally cooling to room temperature to obtain a primary carbon-coated silicon-carbon material;
[0130] Step b, transfer the primary carbon-coated silicon-carbon material prepared above to a secondary carbon-coating device, introduce nitrogen at a nitrogen flow rate of 10 L / min (the nitrogen flow rate is maintained unchanged until the temperature drops to room temperature), expel oxygen until the oxygen content is less than 0.5%, heat the temperature to 600°C at a rate of 5°C / min, and begin to introduce acetylene at a flow rate of 2 L / min for 3 hours, stop introducing acetylene, and naturally cool to room temperature to obtain a secondary carbon-coated silicon-carbon material.
[0131] Example 8
[0132] This embodiment provides a method for preparing a silicon-carbon material, comprising the following steps:
[0133] Step a, weighing 1.5322 kg of the porous carbon prepared in Example 2, that is, the mass of the dry porous carbon without water is 1.5 kg, transferring it to a vapor deposition silicon equipment, introducing nitrogen, the nitrogen flow rate is 10 L / min (the nitrogen flow rate is maintained until the temperature drops to room temperature), exhausting oxygen until the oxygen content is less than 0.5%, heating to 600° C. at a rate of 10° C. / min, introducing monosilane, the monosilane flow rate is 3 L / min, the introduction time is 3 h, stopping the introduction of monosilane, and heating to 700° C. at a rate of 10° C. / min, starting to introduce acetylene, the acetylene flow rate is 4 L / min, the introduction time is 2 h, stopping the introduction of acetylene, and naturally cooling to room temperature to obtain a primary carbon-coated silicon-carbon material;
[0134] Step b, transfer the primary carbon-coated silicon-carbon material prepared above to a secondary carbon-coating device, introduce nitrogen at a nitrogen flow rate of 15 L / min (the nitrogen flow rate is maintained unchanged until the temperature drops to room temperature), expel oxygen until the oxygen content is less than 0.5%, heat the temperature to 700°C at a rate of 10°C / min, and begin to introduce acetylene at a flow rate of 4 L / min for 2 hours, stop introducing acetylene, and naturally cool to room temperature to obtain a secondary carbon-coated silicon-carbon material.
[0135] Example 9
[0136] This embodiment provides a method for preparing a silicon-carbon material, comprising the following steps:
[0137] Step a, weighing 1.5306 kg of the porous carbon prepared in Example 3, that is, the mass of the dry porous carbon without water is 1.5 kg, transferring it to a vapor deposition silicon equipment, introducing nitrogen, the nitrogen flow rate is 20 L / min (the nitrogen flow rate is maintained until the temperature drops to room temperature), exhausting oxygen until the oxygen content is less than 0.5%, heating to 500° C. at a rate of 8° C. / min, introducing monosilane, the monosilane flow rate is 4 L / min, the introduction time is 4 h, stopping the introduction of monosilane, and heating to 600° C. at a rate of 8° C. / min, starting to introduce acetylene, the acetylene flow rate is 3 L / min, the introduction time is 4 h, stopping the introduction of acetylene, and naturally cooling to room temperature to obtain a primary carbon-coated silicon-carbon material;
[0138] Step b, transfer the primary carbon-coated silicon-carbon material prepared above to a secondary carbon-coating device, introduce nitrogen at a nitrogen flow rate of 20 L / min (the nitrogen flow rate is maintained unchanged until the temperature drops to room temperature), exhaust oxygen until the oxygen content is less than 0.5%, heat the temperature to 600°C at a rate of 8°C / min, and begin to introduce acetylene at a flow rate of 3 L / min for 4 hours, stop introducing acetylene, and naturally cool to room temperature to obtain a secondary carbon-coated silicon-carbon material.
[0139] Example 10
[0140] This embodiment provides a method for preparing a silicon-carbon material, comprising the following steps:
[0141] Step a, weighing 1.5416 kg of the porous carbon prepared in Example 4, that is, the mass of the dry porous carbon without water is 1.5 kg, transferring it to a vapor deposition silicon equipment, introducing nitrogen, the nitrogen flow rate is 5 L / min (the nitrogen flow rate is maintained until the temperature drops to room temperature), exhausting oxygen until the oxygen content is less than 0.5%, heating to 450°C at a rate of 2°C / min, introducing monosilane, the monosilane flow rate is 1 L / min, the introduction time is 6 hours, stopping the introduction of monosilane, and heating to 500°C at a rate of 2°C / min, starting to introduce acetylene, the acetylene flow rate is 4 L / min, the introduction time is 1 hour, stopping the introduction of acetylene, and naturally cooling to room temperature to obtain a primary carbon-coated silicon-carbon material;
[0142] Step b, transfer the primary carbon-coated silicon-carbon material prepared above to a secondary carbon-coating device, introduce nitrogen at a nitrogen flow rate of 5 L / min (the nitrogen flow rate is maintained unchanged until the temperature drops to room temperature), exhaust oxygen until the oxygen content is less than 0.5%, heat the temperature to 500°C at a rate of 2°C / min, and begin to introduce acetylene at a flow rate of 4 L / min for 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a secondary carbon-coated silicon-carbon material.
[0143] Embodiment 11
[0144] This embodiment provides a method for preparing a silicon-carbon material, comprising the following steps:
[0145] Step a, weighing 1.5275 kg of the porous carbon prepared in Example 5, that is, the mass of the dry porous carbon without water is 1.5 kg, transferring it to a vapor deposition silicon equipment, introducing nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate is maintained until the temperature drops to room temperature), exhausting oxygen until the oxygen content is less than 0.5%, heating to 700°C at a rate of 25°C / min, introducing monosilane, the monosilane flow rate is 5 L / min, the introduction time is 2h, stopping the introduction of monosilane, and heating to 750°C at a rate of 25°C / min, starting to introduce acetylene, the acetylene flow rate is 1 L / min, the introduction time is 5h, stopping the introduction of acetylene, and naturally cooling to room temperature to obtain a primary carbon-coated silicon-carbon material;
[0146] Step b, transfer the primary carbon-coated silicon-carbon material prepared above to a secondary carbon-coating device, introduce nitrogen at a nitrogen flow rate of 30 L / min (the nitrogen flow rate is maintained unchanged until the temperature drops to room temperature), exhaust oxygen until the oxygen content is less than 0.5%, heat the temperature to 750°C at a rate of 25°C / min, and begin to introduce acetylene at an acetylene flow rate of 1 L / min for 5 hours, stop introducing acetylene, and naturally cool to room temperature to obtain a secondary carbon-coated silicon-carbon material.
[0147] Example 12
[0148] This embodiment provides a method for preparing a silicon-carbon material, comprising the following steps:
[0149] Step a, weighing 1.5369 kg of the porous carbon prepared in Example 6, that is, the mass of the dry porous carbon without water is 1.5 kg, transferring it to a vapor deposition silicon equipment, introducing nitrogen, the nitrogen flow rate is 25 L / min (the nitrogen flow rate is maintained until the temperature drops to room temperature), exhausting oxygen until the oxygen content is less than 0.5%, heating to 550° C. at a rate of 15° C. / min, introducing monosilane, the monosilane flow rate is 3 L / min, the introduction time is 4 h, stopping the introduction of monosilane, and heating to 650° C. at a rate of 5° C. / min, starting to introduce acetylene, the acetylene flow rate is 3 L / min, the introduction time is 2 h, stopping the introduction of acetylene, and naturally cooling to room temperature to obtain a primary carbon-coated silicon-carbon material;
[0150] Step b, transfer the primary carbon-coated silicon-carbon material prepared above to a secondary carbon-coating device, introduce nitrogen at a nitrogen flow rate of 15 L / min (the nitrogen flow rate is maintained unchanged until the temperature drops to room temperature), expel oxygen until the oxygen content is less than 0.5%, heat the temperature to 650°C at a rate of 5°C / min, and begin to introduce acetylene at a flow rate of 3 L / min for 2 hours, stop introducing acetylene, and naturally cool to room temperature to obtain a secondary carbon-coated silicon-carbon material.
[0151] Comparative Example 1
[0152] This comparative example provides a method for preparing porous carbon, comprising the following steps:
[0153] Step a, crushing coconut shell charcoal to a D50 of 8 μm, mixing it with potassium hydroxide in a mass ratio of 1:1, heating the obtained mixture to 850° C. at a rate of 5° C. / min under a nitrogen atmosphere for 3 hours, and cooling to room temperature to obtain a composite material of carbon material and metal derivative;
[0154] Step b, acid-washing and water-washing the composite material until the pH of the water washing solution is 6, filtering and collecting the porous carbon and drying it, heating the dried porous carbon to 900° C. at a rate of 5° C. / min under a nitrogen atmosphere for 3 h to obtain deoxidized porous carbon;
[0155] Step c, subjecting the deoxidized porous carbon to graded treatment to obtain finished porous carbon with D0 of 2 μm, D50 of 7 μm and D100 of 18 μm.
[0156] The finished porous carbon prepared above was prepared in exactly the same manner as in Example 7 to obtain a silicon-carbon material.
[0157] Comparative Example 2
[0158] This comparative example provides a method for preparing porous carbon, comprising the following steps:
[0159] Step a, crushing the carbonized phenolic resin material (the phenolic resin powder is kept at 600°C for 3 hours under a nitrogen atmosphere) to a D50 of 8 μm, mixing it with potassium hydroxide in a mass ratio of 1:1, heating the obtained mixture to 850°C at a rate of 5°C / min under a nitrogen atmosphere for 3 hours, and cooling to room temperature to obtain a composite material of a carbon material and a metal derivative;
[0160] Step b, acid-washing and water-washing the composite material until the pH of the water washing solution is 6, filtering and collecting the porous carbon and drying it, heating the dried porous carbon to 900° C. at a rate of 5° C. / min under a nitrogen atmosphere for 3 h to obtain deoxidized porous carbon;
[0161] Step c, subjecting the deoxidized porous carbon to graded treatment to obtain finished porous carbon with D0 of 2 μm, D50 of 7 μm and D100 of 18 μm.
[0162] The finished porous carbon prepared above was prepared in exactly the same manner as in Example 7 to obtain a silicon-carbon material.
[0163] Comparative Example 3
[0164] This comparative example provides a method for preparing porous carbon, comprising the following steps:
[0165] Step a, crushing petroleum coke to a D50 of 8 μm, mixing the petroleum coke with potassium hydroxide in a mass ratio of 1:1, heating the obtained mixture to 850° C. at a rate of 5° C. / min under a nitrogen atmosphere for 3 hours, and cooling to room temperature to obtain a composite material of carbon material and metal derivative;
[0166] Step b, acid-washing and water-washing the composite material until the pH of the water washing solution is 6, filtering and collecting the porous carbon and drying it, heating the dried porous carbon to 900° C. at a rate of 5° C. / min under a nitrogen atmosphere for 3 h to obtain deoxidized porous carbon;
[0167] Step c, subjecting the deoxidized porous carbon to graded treatment to obtain finished porous carbon with D0 of 2 μm, D50 of 7 μm and D100 of 18 μm.
[0168] The finished porous carbon prepared above was prepared in exactly the same manner as in Example 7 to obtain a silicon-carbon material.
[0169] Comparative Example 4
[0170] This comparative example provides a method for preparing porous carbon, comprising the following steps:
[0171] S1, dissolving sodium gluconate in water under a nitrogen atmosphere, wherein the concentration of sodium gluconate is 3 mol / L, and heating the solution under a nitrogen atmosphere to remove water to obtain sodium gluconate;
[0172] S2 to S5 are the same as those in Example 1 and will not be described in detail here.
[0173] The finished porous carbon prepared above was prepared in exactly the same manner as in Example 7 to obtain a silicon-carbon material.
[0174] Comparative Example 5
[0175] This comparative example provides a method for preparing porous carbon, comprising the following steps:
[0176] S1, dissolving sodium citrate in water under a nitrogen atmosphere, wherein the concentration of the sodium citrate is 3 mol / L, and heating the solution under a nitrogen atmosphere to remove water to obtain sodium citrate;
[0177] S2 to S5 are the same as those in Example 1 and will not be described in detail here.
[0178] The finished porous carbon prepared above was prepared in exactly the same manner as in Example 7 to obtain a silicon-carbon material.
[0179] Comparative Example 6
[0180] This comparative example provides a method for preparing porous carbon, comprising the following steps:
[0181] S1, dissolving sodium benzoate in water under a nitrogen atmosphere, wherein the concentration of sodium benzoate is 3 mol / L, and heating the solution under a nitrogen atmosphere to remove water to obtain sodium benzoate;
[0182] S2 to S5 are the same as those in Example 1 and will not be described in detail here.
[0183] The finished porous carbon prepared above was prepared in exactly the same manner as in Example 7 to obtain a silicon-carbon material.
[0184] Comparative Example 7
[0185] This comparative example provides a method for preparing porous carbon, comprising the following steps:
[0186] S1 to S4 are the same as those in Example 1 and will not be described in detail here;
[0187] S5, crushing and classifying the deoxidized porous carbon to obtain a finished porous carbon with D0 of 0.2 μm, D50 of 7 μm and D100 of 18 μm.
[0188] Comparative Example 8
[0189] This comparative example provides a method for preparing porous carbon, comprising the following steps:
[0190] S1 to S4 are the same as those in Example 1 and will not be described in detail here;
[0191] S5, crushing and classifying the deoxidized porous carbon to obtain a finished porous carbon with D0 of 2 μm, D50 of 7 μm, and D100 of 40 μm.
[0192] The porous carbons prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were characterized, and the results are shown in Table 1.
[0193] Table 1
[0194]
[0195] Application Examples
[0196] The silicon-carbon materials prepared in the above-mentioned Examples 7 to 12 and Comparative Examples 1 to 8 are respectively assembled into batteries, and the specific steps are as follows:
[0197] (1) Preparation of negative electrode sheet: 2.5g N-methylpyrrolidone and 0.1g polyvinylidene fluoride were mixed evenly to obtain a transparent viscous solution, and then 0.1g conductive carbon black Super P was added and dispersed evenly, and 0.8g negative electrode material was added and dispersed evenly to obtain a black viscous slurry, wherein the negative electrode material is a mixed material (mass ratio of the two is 1:9) after the prepared silicon carbon material and graphite material (1.5V charging capacity 355mAh / g, first coulomb efficiency 93.6%) are mixed evenly. The black viscous slurry is evenly coated on the surface of the copper foil with a scraper to form a film with a coating thickness of 100μm, and then dried at 90°C, rolled and cut into 14mm diameter discs and weighed for standby use.
[0198] (2) Assembly of lithium-ion batteries: A metal lithium sheet with a diameter of 15.8 mm and a thickness of 100 μm was used as the counter electrode, a Celgard 2400 with a diameter of 16 mm and a thickness of 25 μm was used as the separator, the 14 mm negative electrode sheet prepared above was used as the working electrode, and a solution of 1 mol / L LiPF6 dissolved in ethylene carbonate and ethyl methyl carbonate (volume ratio 3:7) was used as the electrolyte to assemble a 2032-type button cell. Six batteries were assembled for each negative electrode material, and a total of six groups of data were tested. After removing the highest and lowest data, the average of the remaining four groups of data was taken as the battery performance data.
[0199] (3) The specific test conditions for the performance of button cells are as follows: at room temperature of 25°C, using a blue electric tester, the assembled button cell is discharged to 0.005V at 0.1C (1C corresponds to 450mAh / g), left to stand for 5 minutes, and then discharged to 0.005V at 0.05C. After another 5 minutes of standing, the discharge procedure is terminated by discharging to 0.005V at 0.02C. After standing for 5 minutes, the cell is charged to 1.5V at 0.1C. The ratio of the charge capacity to the discharge capacity is the first coulombic efficiency at 1.5V. Further, the cell is discharged to 0.005V at 0.2C, left to stand for 5 minutes, then discharged to 0.005V at 0.05C, left to stand for 5 minutes, and then charged to 1.5V at 0.2C. The ratio of the charge capacity after 50 cycles of this process to the first charge capacity (the first time charged at 0.2C) is the capacity retention rate. On the other hand, the first cycle full charge expansion rate is obtained by testing the ratio of the electrode thickness after the first cycle of charging (thickness without copper foil) to the electrode thickness before the cycle (thickness without copper foil). The results are shown in Table 2.
[0200] Table 2
[0201]
[0202]
[0203] The results show that the charging specific capacity, charging coulomb efficiency, capacity retention rate and first week full charge expansion rate of the lithium ion batteries added with the silicon-carbon materials prepared in Examples 7 to 12 of the present invention are better than those of Comparative Examples 1 to 8, which proves that the silicon-carbon material prepared with the porous carbon provided by the present invention as the negative electrode material can significantly improve the electrochemical performance and cycle life of lithium ion batteries, which is of great significance to the development of lithium ion batteries.
[0204] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing porous carbon, characterized in that: The steps include: S1, calcining the phenol metal salt at 600°C to 1100°C for 1h to 5h under a protective atmosphere to obtain a carbon-based material; S2, crushing the carbon-based material to a D50 value of 3 μm to 15 μm; S3, testing the ash content of the crushed carbon-based material. If the ash content is ≤0.2%, directly proceed to S4; if the ash content is >0.2%, acid washing and water washing are performed on the crushed carbon-based material for several times until the ash content of the carbon-based material is ≤0.2% or the pH of the water washing liquid is <7; S4, testing the oxygen content of the crushed carbon material, if the oxygen content is ≤0.05mmol / g, directly proceed to S5; if the oxygen content is >0.05mmol / g, calcining the crushed carbon material at 700℃~1200℃ for 0.5h~3h under protective atmosphere and then proceed to S5; S5, testing the particle size of the carbon material in S4, if it meets the requirements of D0 of 1μm to 5μm, D50 of 3μm to 15μm, and D100 of 10μm to 30μm, no further processing is required; if it does not meet the above particle size requirements, the carbon material is crushed and graded until the particle size meets the requirements to obtain porous carbon.
2. The method for preparing porous carbon according to claim 1, characterized in that: In S1 and S4, the protective atmosphere gas is one or more of nitrogen, argon, helium, carbon dioxide or water vapor; and / or In S1, the temperature is raised to 600°C to 1100°C at a rate of 2°C / min to 25°C / min; and / or In S1, the metal phenolate is one or more of lithium phenolate, sodium phenolate, potassium phenolate, magnesium phenolate, calcium phenolate, zinc phenolate, manganese phenolate, aluminum phenolate or iron phenolate; and / or In S3, the pickling is carried out using one or more of hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, hydrobromic acid, phosphoric acid, perchloric acid, formic acid or acetic acid; and / or In S4, the temperature is increased to 700°C to 1200°C at a rate of 2°C / min to 25°C / min.
3. The method for preparing porous carbon according to claim 1 or 2, characterized in that: In S1, the preparation method of the phenol metal salt comprises the following steps: adding phenol and a metal source into a solvent, mixing them evenly, and removing the solvent to obtain the phenol metal salt; wherein the metal source comprises one or more of metal oxides or hydroxides corresponding to lithium, sodium, potassium, magnesium, calcium, zinc, manganese, aluminum, and iron; or In S1, the preparation method of the phenol metal salt comprises the following steps: adding phenol and a metal source into a solvent, reacting, and removing the solvent to obtain the phenol metal salt; wherein the metal salt comprises one or more of the single substances or metal hydrides corresponding to lithium, sodium, potassium, magnesium, calcium, zinc, manganese, aluminum, and iron; or In S1, the preparation method of the phenol metal salt comprises the following steps: reacting molten phenol with a solid metal source in air or an inert atmosphere to obtain a phenol metal salt; wherein the solid metal source comprises one or more of metal oxides or hydroxides corresponding to lithium, sodium, potassium, magnesium, calcium, zinc, manganese, aluminum, and iron.
4. A porous carbon, characterized in that The porous carbon is prepared by the method for preparing the porous carbon according to any one of claims 1 to 3.
5. A silicon-carbon material, characterized in that: The porous carbon comprises the porous carbon as claimed in claim 4.
6. A method for preparing the silicon-carbon material according to claim 5, characterized in that: The steps include: Step a, depositing silicon particles onto the surface and / or pores of the porous carbon by chemical vapor deposition to obtain a silicon-carbon material precursor; Step b, subjecting the silicon-carbon material precursor to one-step carbon coating or two-step carbon coating to obtain a carbon-silicon material.
7. A negative electrode, characterized in that Including the silicon-carbon material as described in claim 5.
8. Use of the silicon-carbon material according to claim 5 or the negative electrode according to claim 7 in the preparation of a lithium-ion battery.
9. A lithium ion battery, characterized in that: Includes the silicon-carbon material according to claim 5 or the negative electrode according to claim 7.
10. A battery module, characterized in that: Includes the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of porous composite material and carbon material
CN103723702A
Preparation method of B and N co-doped sodium-rich porous carbon and application of B and N co-doped sodium-rich porous carbon in sodium-ion battery
CN115440983A
Silicon-carbon negative electrode material for battery and preparation method of silicon-carbon negative electrode material
CN117878276A
Continuous process for manufacturing hierarchically porous carbon material
US20220289573A1
Silicon-carbon negative electrode material for lithium ion battery and preparation method therefor
US20230135178A1
Cited By
Graded graphitization degree porous carbon material, silicon-carbon composite negative electrode material, preparation method and application
CN121134759A
Hierarchically graphitized porous carbon material, silicon-carbon composite negative electrode material, preparation method and application
CN121134759B